Research highlights: detecting, characterizing and quantifying the presence and impact of carbon nanomaterials in environmental systems. Issue 4 (30th August 2015) - Pettibone, John M.; Louie, Stacey M.
<x xml:space="preserve">Abstract</x> We highlight articles examining different aspects contributing to the fate and role of carbon nanomaterials in environmental systems.